Influence the intensity of industrial relations on the innovative activity. Case of Lubuskie voivodeship in 2008-2010 = Wpływ intensywności powiązań przemysłowych na aktywność innowacyjną. Przypadek województwa lubuskiego w latach 2008-2010 - Świadek, Arkadiusz (Zielona Góra: Faculty of Economics and Management Press)
The main objective of the study was an attempt to search for the conditions affect the intensity of supply chains for enterprises innovative activity within the regional industrial system, and consequently determine the directions for the model of regional system of innovation, taking into account the specificities of Lubuskie Region. The study was based on a questionnaire on a group of 545 companies from Silesia. The study used probity modeling. This method is an effective research tool for large, but the static tests in which the dependent variable has a qualitative character.
Keywords: innowacja; przemysł; region; innovation; industry